Study on insulation performance of environmental protection C5-PFK gas mixture based on time sharing and mutual fiber sensing detection technology. Issue 1 (July 2021) - Shiling, Zhang
Abstract: With the proposal of China's goal of carbon peak and carbon neutralization, it is urgent for C5-PFK environment-friendly gas insulating medium to replace SF6 in key power equipment, and the research on C5-PFK mixed gas on-line detection technology should be carried out in advance. In view of this, this project is the first time to apply the time-sharing mutual optical fiber sensing detection technology to the C5-PFK mixed gas insulation and decomposition performance research. Theoretical and software analysis: the insulation and decomposition characteristics of C5-PFK gas mixture were simulated from the molecular dynamics level. The variation of absorption spectrum with the temperature and pressure was simulated by self programming simulation software platform, and coupling field distribution of electric power equipment in C5-PFK insulation environment was obtained. The grey system and the NSGA-II hybrid algorithm are applied to inverse and predict the decomposed gas concentration high coupling and nonlinear data series. Hardware and device development: develop a time-sharing and interactive optical fiber live detection device to achieve quantitative online acquisition of decomposition components of mixed gas. Build a real test platform for testing the power frequency, lightning and switching impulse performance of gas mixture. The influence of high frequency vibration and large temperature difference on the experimental results is solved by optimizing the optical system through structure iteration. The time-sharing and interactive optical fiber sensing detection technology can realize the detection of C5-PFK mixed gas with high sensitivity and wide concentration range, which provides theoretical and experimental basis for China's dual carbon target construction demonstration project, and has good economic and social benefits.